Psychological engagement drives brand loyalty: evidence from Malaysian ecotourism destinations - Quoquab, Farzana (Emerald Group Holdings Ltd., 2021)
Purpose: The present study attempts to shed some light on tourists’ destination brand loyalty (DBL) in the Malaysian ecotourism context. More specifically, this study aims to examine the relationships between electronic word of mouth (eWOM), destination brand quality (DBQ), destination brand image (DBI), psychological engagement (PE) and DBL. Design/methodology/approach: Based on the Stimulus–Organism–Response theory and buyer black box model, this study developed a framework to address tourists’ loyalty towards ecotourism destinations. An online survey was carried out to collect data, which yielded 210 completed usable responses. Structural equation modelling – partial least squares was used to test the study hypotheses. Findings: Findings from this study revealed that eWOM and destination product quality affect DBI. Moreover, data support the mediating effect of PE between DBI and DBL. Practical implications: This study provides valuable insights for practitioners and policymakers of the tourism industry in creating a DBI, keeping tourists psychologically engaged and retaining their loyalty to the ecotourism destinations. Originality/value: This study is amongst the first to examine the effect of eWOM and DBQ on DBI in the ecotourism context. It also examines PE in relation to the DBI, which is a comparatively new area in the literature.